Potential official sector gold holdings in rapidly growing and highly open East Asian economies. - Chan, Geok Hoon. (2008)
We will be examining the possible rationales behind this underweighted gold holding policy which is widely practiced in East Asia and the impact of such policy on the monetary and financial well-being of the East Asian economies. From our findings, we will examine the potential of gold in these economies and the reasons for the potential increase in the ratio of gold holdings to the total reserves on these countries.